Pathways to integrate Indigenous and local knowledge in ocean governance processes: Lessons from the Algoa Bay Project, South Africa - Rivers, Nina; Strand, Mia; Fernandes, Meredith; Metuge, Denning; Lemahieu, Anne; Nonyane, Chilo Loyolah; Benkenstein, Alex; Snow, Bernadette (Frontiers in Marine Science, 2023)
Current coastal and ocean management approaches do not adequately acknowledge and integrate Indigenous and Local Knowledge (ILK). This is problematic because how humans value and perceive coastal and marine resources is integrally linked to how they use and manage these resources, especially in adapting to social-ecological change. Coastal and marine resources are situated within complex social-ecological systems that are culturally, economically, historically and politically embedded. Therefore, management approaches have to integrate transdisciplinary and contextual perspectives in order to be relevant, sustainable and adaptive. Following extensive research in Algoa Bay, South Africa, through a bottom-up and top-down research process of working with ILK users as well as coastal authorities and decision-makers in tandem, this article highlights several pathways to bridge the gap between existing ILK and current coastal and ocean management approaches. ILK coastal users, managers and decision-makers were brought together to co-identify and develop these pathways collaboratively, which included: adopting contextual approaches to management; increasing transparency and communication between coastal authorities and users; increasing access to relevant and useable information; reviewing and amending relevant marine spatial planning (MSP) legislation towards a stronger connection between MSP and Indigenous knowledge legislation; as well as amending legislation pertaining to access to coastal and marine areas. ILK coastal communities want to be meaningfully included in how their coastline and ocean resources are managed and also seek increased access to coastal areas. By highlighting pathways to include ILK and the knowledge holders themselves, this paper seeks to contribute to improved protection and sustainable management of marine resource use.